Beauty Standard di Era Digital: Hubungan Social Comparison dan Body Image dengan Kepercayaan Diri Remaja - Rahmadani Saputri; Any Nurhayaty; Daffa Tiara Kurnia Prastiwi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This study is motivated by the growing use of social media among adolescents, which fosters social comparison and body image formation that may influence self-confidence. Adolescence is a crucial developmental phase in which identity formation is highly shaped by exposure to social and aesthetic standards in digital environments. This research aims to analyze the relationship between social comparison and body image toward adolescents’ self-confidence on social media. A quantitative correlational approach was applied to 400 adolescents aged 17–19 years in Indonesia who actively use social media for at least two hours per day. The instruments included validated and reliable scales of social comparison, body image, and self-confidence. Data were analyzed using multiple linear regression with SPSS version 25.0. The results indicate that social comparison and body image have a positive and significant effect on adolescents’ self-confidence (p < 0.001), with an R² value of 0.602, meaning both variables explain 60.2% of the variance in self-confidence. These findings suggest that social comparison is not always detrimental but can serve as a motivational mechanism when conducted adaptively. The study highlights the importance of digital literacy and positive self-image education for adolescents to foster healthy self-confidence in the digital age.